Policy Analysis of Religious Moderation by the Ministry of Religious Affairs from an Institutional Perspective - Faisal Luqman Hakim; Shaleh, Shaleh; Prasitya, Ahmad Padli (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2025)
This study examines how ministerial policies on religious moderation are institutionally integrated and effectively implemented within State Islamic Higher Education Institutions (Perguruan Tinggi Keagamaan Islam Negeri, hereafter PTKIN). The research aims to analyze the alignment between national policy directives and institutional practices at the university level. Using a qualitative case study design, data were collected through observation, in-depth interviews, and documentation. The data were analyzed using the Miles, Huberman, and Saldaña interactive model, with validity ensured through triangulation. The findings reveal two key results. First, although the Ministry of Religious Affairs has formally incorporated religious moderation into institutional planning at PTKIN, the lack of detailed technical guidelines and standardized implementation mechanisms has led to fragmented practices. Second, institutional factors such as the Ministry’s hierarchical structure, the quality of human resources, and an academically grounded culture of religious moderation facilitate policy realization but are constrained by weak internal monitoring and the absence of a binding legal framework. These findings highlight the need to translate normative policy commitments into enforceable institutional mechanisms, particularly within higher education systems characterized by administrative decentralization and academic autonomy.